Asuhan Keperawatan Pada Tn.S Dengan Halusinasi PendengaranDi RSJ Prof DR Soerojo Magelang - Dini Melinda Eka Pratiwi; Ririn Sundari (Universitas Pekalongan, 2022)
Hallucinations are a form of reality orientation disorder characterized by a person giving a response or judgment in the absence of a stimulus received by the senses, and is one of the effects of perceptual disturbances. The purpose of this study is to provide nursing care to clients with impaired sensory perception of hearing with dhikr and istigfar therapy. The method used by the researcher is a qualitative study using case study research (case studies) with a nursing process approach in one patient who has sensory perception disorders. The process of collecting data by interviewing, observing and viewing the patient's medical records. Data analysis was carried out by data collection and data reduction. The results of the research that all interventions have been successfully carried out and nursing problems are resolved as shown by the patient being able to control his auditory hallucinations with dhikr and istigfar. Spiritual Therapy with Islamic dhikr and istigfar, which is a treatment and treatment aimed at healing a mental illness, to each individual, with inner or spiritual strength, in the form of religious rituals not treatment with drugs, with the aim of strengthening one's faith so that he can develop his potential and religious nature to the fullest. So it can be concluded that the application of dhikr therapy can control the auditory hallucinations experienced by the client.